Urban Toponymy as Flood Memory: Analyzing Water-Related Place Names in Jakarta, Indonesia - Mulyadi, Asep; Dede, Moh.; Widiawaty, Millary Agung; Nurbayani, Siti; Sustiati, Heni; Anshari, Bayu Iqbal; Ismail, Arif (Forum for Linguistic Studies, 2025)
Jakarta, Indonesia's flood-prone capital, bears a hydrological legacy embedded in its place names (toponyms). This study examines how urban village toponyms reflect historical water-related landscapes and their implications for contemporary flood risk. This study examines the relationship between Jakarta's toponyms and its flooding patterns through qualitative descriptive analysis of 104 urban village names identified in flood-prone zones by Jakarta's Bureau of Regional Disaster Management (BPBD Jakarta). We identified 14 toponyms explicitly referencing rivers, 27 tied to water-associated vegetation, and 7 denoting wetlands, revealing a strong correlation between toponyms and ancestral ecological knowledge. Toponymic data collected from the Indonesia Statistics Agency (BPS) and the Dutch East-Indies Topographic Maps reveals diverse linguistic origins including Malay-Betawi, Javanese, Sundanese, Chinese, Portuguese, and Dutch. From 1940 to 2019, landscape transformation analysis demonstrates that today's flood-vulnerable neighborhoods are primarily built on former wetlands, lakes, and agricultural fields, often erasing original toponyms. Historically, toponyms like Danau Sunter or Rawabadak served as implicit flood hazard indicators, yet modern development has disregarded these warnings. We argue that toponym conservation, supported by historical maps and legal frameworks, can preserve indigenous knowledge for disaster mitigation. Water-related names underscore how toponyms encode landscape vulnerabilities now obscured by urbanization. This study highlights the urgency of integrating toponymic wisdom into spatial planning to reinforce flood resilience in rapidly transforming cities, where cultural memory and environmental risk intersect.